A Study on Retail Investors’ Awareness of Stock Market Investments in Delhi-NCR - Chand, Tek (Indian Journal of Research in Capital Markets, 2022)
The stock market is considered an essential component of an economy. It plays a vital role in a country’s economy in terms of spending and investment. It helps investors earn income when investing in the stock market (Stock market investment: 10 things, 2018). The present study aimed to study retail investors’ awareness of stock market investments. The data were collected from 120 retail investors of Delhi-NCR using a standard well-structured Google survey questionnaire. The analysis was made by using statistical tools like percentage, rank, and chi-square test. The study proved that male participation was higher as compared to female. Besides, the study also found a significant difference in the demographic variables of the retail investors’ i.e., academic qualification and income groups with respect to awareness about investing in the stock market (Agarrwal & Jain, 2021).